Exploration of Factors Forming Intention to Buy Skincare among Millennial Generation Male Consumers in Bandung, Indonesia - Ashila Dwiyanisa (Jurnal Computech & Bisnis (e-journal), 2022)
Men's grooming is growing, and data confirms that sales of men's facial creams have doubled, and the use of men's facial cleansing products in India has jumped 60-fold between 2009-2016. During the Covid-19 pandemic, many industries, including the beauty industry, were negatively affected. However, the local beauty industry sector continues to emerge in Indonesia. Beauty and body care products are one of the business units that have enlivened the Indonesian industrial sector. The projection of the Indonesian skincare product market for the 2020-2027 period, the male and millennial generations will experience the fastest growth. The sampling method is based on a non-probability sampling technique with a judgmental sampling technique. The sample was taken based on the criteria formulated, namely the millennial generation men in Bandung, with an age range determined according to the criteria. The data analysis technique uses factor analysis or Exploratory Factor Analysis (EFA) with SPSS tools. The approach with oblique rotation can accurately model uncorrelated and correlated factors effectively. The results of the factor analysis test in this study have a KMO and Bartlett's Test value of 0.888 with a significance of 0.000. This value indicates that 88.8% of the research instruments analyzed indicate that the skincare purchase intention instrument has a suitable model in testing factor analysis. In conclusion, companies engaged in skincare have an excellent opportunity to target the millennial generation male target market in Bandung because the need for skincare products and the level of awareness to take care of yourself is pretty high. The results of data processing produced ten factors, namely the first factor, "Belief in Product Attributes," the second factor, "Attitude," the third factor, "Product Halal Certification," the fourth factor, "Health," the fifth factor "Subjective Norms," the sixth factor "Environmental Awareness," the seventh factor is "Self Image," the eighth factor is "Perceived Behavioral Control," the ninth factor is "Aging Effect" and the tenth factor is "Repurchase Intention and Environmental Awareness."